2020
DOI: 10.3390/ma13081909
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure Characteristics of Al3Sc1−xZrx Nanoparticles and Their Effects on Mechanical Property and SCC Behavior of Al–Zn–Mg Alloys

Abstract: The Nanostructure characteristics of Al3Sc1−xZrx nanoparticles and their effects on the mechanical properties and stress corrosion cracking (SCC) behavior of Al–Zn–Mg alloys were investigated by 3D atom probe analyses, high-angle annular-dark-field scanning transmission electron microscopy methods, electron back scattered diffraction techniques, electrochemical measurements, slow strain rate tests and quantitative calculations. The results show that adding small amounts of scandium (0.10 percent by weight) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In our study, after one-stage heterogenization, the hardness of Alloy A aged for 96 h was 75.4 ± 0.4 HRB, while for two-stage heterogenization, the hardness of Alloy A aged for 96 h was 73.7 ± 0.4 HRB. Deng [ 35 ] investigated the effects of Al 3 Sc 1−x Zr x nanoparticles on the mechanical properties of aged Al-5.2Zn-1.82Mg alloy and found that the Al 3 Sc 1−x Zr x particles improved the yield strength by 161 ± 7 MPa (40 ± 3 percent) and increased the ultimate tensile strength by 122 ± 4 MPa (27 ± 1 percent). Due to the addition of Zr, Alloy B exhibited a relatively higher hardness of around 76.5 ± 0.4 HRB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, after one-stage heterogenization, the hardness of Alloy A aged for 96 h was 75.4 ± 0.4 HRB, while for two-stage heterogenization, the hardness of Alloy A aged for 96 h was 73.7 ± 0.4 HRB. Deng [ 35 ] investigated the effects of Al 3 Sc 1−x Zr x nanoparticles on the mechanical properties of aged Al-5.2Zn-1.82Mg alloy and found that the Al 3 Sc 1−x Zr x particles improved the yield strength by 161 ± 7 MPa (40 ± 3 percent) and increased the ultimate tensile strength by 122 ± 4 MPa (27 ± 1 percent). Due to the addition of Zr, Alloy B exhibited a relatively higher hardness of around 76.5 ± 0.4 HRB.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, after one-stage heterogenization, the hardness of Alloy A aged for 96 h was 75.4 ± 0.4 HRB, while for two-stage heterogenization, the hardness of Alloy A aged for 96 h was 73.7 ± 0.4 HRB. Deng [35] investigated the effects of Al3Sc1−xZrx nanoparticles on the mechanical properties of aged…”
Section: Hardness and Tensile Propertiesmentioning
confidence: 99%
“…Sc is supposed to make alloying elements more ductile at high temperatures. The aluminium scandium's solid solubility changes greatly with temperature [7]. It also deforms at a high strain rate despite having a higher diffusivity.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum (Al) alloys are widely used in various industries. The addition of rare earth elements to Al alloys has been proven to have optimal effects [1][2][3][4][5][6][7]. Among Al alloy elements, scandium (Sc) is one of the most effective elements for Al reinforcement.…”
Section: Introductionmentioning
confidence: 99%